The Impact of Fluctuations in Fuel Prices and the Rupiah Exchange Rate on the Operational Management Efficiency of Shipping Companies - Dony Ari Nugroho; Sofyan Halim (Institut Manajemen Wiyata Indonesia, 2026)
Fuel oil (BBM) prices and the rupiah exchange rate are two external economic variables that significantly influence the cost structure of shipping companies, particularly in an archipelagic country such as Indonesia. This study aimed to examine the effects of fuel price fluctuations and rupiah exchange rate movements on the efficiency of shipping operational management. The study employed a quantitative descriptive-verification approach using secondary time-series data, including high-speed diesel (HSD) and marine fuel oil (MFO) prices, the rupiah exchange rate against the US dollar, ship fuel consumption, and operational costs per voyage. The data were analyzed using multiple linear regression and could be extended to panel data regression for cross-fleet observations. The results indicated that increases in fuel prices raised ship operational costs and potentially reduced maritime transportation volume, while rupiah depreciation increased the costs of fuel procurement, spare parts, and vessel maintenance due to dependence on imported components. Operational efficiency could be improved through information technology-based fuel consumption monitoring, optimization of vessel economic speed (slow steaming), and budget planning that accounted for exchange rate fluctuations and energy cost sensitivity. This study contributed an operational efficiency strategy framework for shipping companies that is adaptive to energy price pressures and exchange rate volatility.